Subsurface Mapping of Ground Water using Schlumberger Configuration in Upstream of Brantas River, Batu area, East Java, Indonesia - Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2014)
A Resistivity sounding survey of groundwater was performed around the upstream of Brantas river, Batu area, East Java, Indonesia. The goal of this study is to identify the water resources. In order to determine the aquifer thickness and the ground water flow, it was done a mapping in the 6-spring water area, as a representative of 108 spring water in the study area. Acquisitions are taken by six lines using Schlumberger configuration around the spring water at length of measurement line about 400 m with electrode spacing 10 m. Data processing and interpretation were using IP2WIN, Progress 3, and Rockwork 15, which allowed in 1D and 3D scheme to present the distribution of real resistivity below the surface. Interpretation of the results indicate the presence of a layer of rock that is formed due to volcanic activity. The rock structure is composed of volcanic rock breccia, tuff breccia, sandy tuff, tuff and lava. Rocks of volcanic breccia, tuff breccia, tuff and lava have small porosity due to having a small grain size and smooth, and have the low permeability, so it is not able to store and drain water. This rock layer is expected to function as an impermeable layer and can further serve to hold water that can seep into the ground below, so that the ground water will flow horizontally. While sandstone has a great porosity because it has a rounded rock grains with large permeability, so as to save water and running it in a number of significant.